2021
DOI: 10.1177/00048674211062532
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective potential of lithium and role of fractalkine in euthymic patients with bipolar disorder

Abstract: Objective: Over a half century, lithium has been used as the first-line medication to treat bipolar disorder. Emerging clinical and laboratory studies suggest that lithium may exhibit cardioprotective effects in addition to neuroprotective actions. Fractalkine (CX3CL1) is a unique chemokine associated with the pathogenesis of mood disorders and cardiovascular diseases. Herein we aimed to ascertain whether lithium treatment is associated with favorable cardiac structure and function in relation to the reduced C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Our recent study revealed that lithium at therapeutic doses reduced the migration and collagen synthesis ability of cardiac fibroblasts through its inhibitory effects on store-operated Ca 2+ entry [ 13 ]. These findings are in line with those of other clinical studies that have suggested the cardioprotective potential of lithium [ 14 , 15 ]. Although heart failure is the primary cause of sudden cardiac death in patients with bipolar disorder [ 16 ], the role of lithium in REM sleep deprivation-induced cardiac dysfunction remains unclear.…”
Section: Introductionsupporting
confidence: 92%
“…Our recent study revealed that lithium at therapeutic doses reduced the migration and collagen synthesis ability of cardiac fibroblasts through its inhibitory effects on store-operated Ca 2+ entry [ 13 ]. These findings are in line with those of other clinical studies that have suggested the cardioprotective potential of lithium [ 14 , 15 ]. Although heart failure is the primary cause of sudden cardiac death in patients with bipolar disorder [ 16 ], the role of lithium in REM sleep deprivation-induced cardiac dysfunction remains unclear.…”
Section: Introductionsupporting
confidence: 92%
“…Existing data indicate that lithium treatment may reduce the risk of cardiovascular diseases in patients with bipolar disorder (BD) 1–3 . Our recent pilot study demonstrated that longer lithium exposure was associated with favorable diastolic function among patients with BD 4 . The findings suggest that lithium treatment may help prevent heart failure in individuals with BD.…”
Section: Variables With Lithium Treatment (N = 58) Without Lithium Tr...mentioning
confidence: 82%
“…Echocardiography was performed by an experienced board‐certified cardiologist blinded to the clinical data according to our previously published protocol 4,6 . In brief, LV geometric patterns were determined based on the recommendations from the American Society of Echocardiography 7 .…”
Section: Variables With Lithium Treatment (N = 58) Without Lithium Tr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Taipei’s authors showed that patients who received lithium as the maintenance treatment had significantly lower mean values of left ventricular internal diameters at end-diastole and end-systole, higher mean values of mitral valve E/A ratio, and superior performance of global longitudinal strain than those without lithium treatment. As possible mechanisms, they postulate lithium’s effect on cardiac remodeling involving many signaling pathways as well as its influence on a chemokine, fractalkine [ 47 ].…”
Section: Adverse Side Effectsmentioning
confidence: 99%